Ekonomi Syariah Tanpa Sentuhan: Pergeseran Etika Jual Beli Muslim Di Era Self Chekout Digital - Ach Saifullah; Rudy Haryanto; Fadllan . (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Digital transformation in the retail sector has driven the adoption of self checkout systems, enabling transactions to take place without direct interaction between sellers and buyers. Although this system offers efficiency and speed of service, it also alters patterns of social interaction and ethical mechanisms in buying and selling transactions. For Muslim communities, this shift raises questions regarding the validity of contracts (akad), the principle of mutual consent (tarāḍī), and the application of muamalah ethics in digital transactions without human contact. This study aims to analyze the shift in Muslim transactional ethics in the use of digital self checkout systems from the perspective of Islamic economics.This study employs a qualitative approach with a descriptive research design. Data were collected through field observations at modern retail outlets implementing self checkout systems and in-depth interviews with Muslim consumers as users of these systems. The findings indicate that self checkout systems influence three main aspects of Islamic transaction ethics. First, sales contracts are formed digitally and automatically without verbal communication, yet they still fulfill the elements of ijab and qabul through system-based approval. Second, the principle of mutual consent (Tarāḍī) shifts toward fast and instantaneous transaction mechanisms. Third, market interaction ethics tend to decline due to reduced social interaction between sellers and buyers. Nevertheless, the majority of respondents perceive self checkout transactions as permissible, provided that price transparency, clarity of the transaction object, and the absence of deception are ensured.This study concludes that self checkout systems give rise to a new form of Muslim transactional ethics that is mechanical and minimally interactive, yet remains compatible with Islamic economic principles as long as contractual clarity and mutual consent are maintained. These findings imply the need to develop digital transaction systems that are not only technically efficient but also supportive of ethical and moral values within modern Islamic economics.